From lithium to sodium: cell chemistry of room temperature sodium–air and sodium–sulfur batteries - Adelhelm, Philipp; Hartmann, Pascal; Bender, Conrad L.; Busche, Martin; Eufinger, Christine; Janek, Juergen (Beilstein Journal of Nanotechnology, 2015)
Research devoted to room temperature lithium–sulfur (Li/S8) and lithium–oxygen (Li/O2) batteries has significantly increased over the past ten years. The race to develop such cell systems is mainly motivated by the very high theoretical energy density and the abundance of sulfur and oxygen. The cell chemistry, however, is complex, and progress toward practical device development remains hampered by some fundamental key issues, which are currently being tackled by numerous approaches. Quite surprisingly, not much is known about the analogous sodium-based battery systems, although the already commercialized, high-temperature Na/S8 and Na/NiCl2 batteries suggest that a rechargeable battery based on sodium is feasible on a large scale. Moreover, the natural abundance of sodium is an attractive benefit for the development of batteries based on low cost components. This review provides a summary of the state-of-the-art knowledge on lithium–sulfur and lithium–oxygen batteries and a direct comparison with the analogous sodium systems. The general properties, major benefits and challenges, recent strategies for performance improvements and general guidelines for further development are summarized and critically discussed. In general, the substitution of lithium for sodium has a strong impact on the overall properties of the cell reaction and differences in ion transport, phase stability, electrode potential, energy density, etc. can be thus expected. Whether these differences will benefit a more reversible cell chemistry is still an open question, but some of the first reports on room temperature Na/S8 and Na/O2 cells already show some exciting differences as compared to the established Li/S8 and Li/O2 systems.
Keywords: energy storage; lithium–oxygen battery; lithium–sulfur battery; sodium–oxygen battery; sodium–sulfur battery

(untitled) - Zaghib, K.; Mauger, A.; Groult, H.; Goodenough, J. B.; Julien, C. M. (Materials, 2013)

(untitled) - Cabana, J.; Monconduit, L.; Larcher, D.; Rosa Palacin, M. (Adv. Mater., 2010)

(untitled) - Kubota, K.; Yabuuchi, N.; Yoshida, H.; Dahbi, M.; Komaba, S. (MRS Bull., 2014)

(untitled) - Dahbi, M.; Yabuuchi, N.; Kubota, K.; Tokiwa, K.; Komaba, S. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Ellis, B. L.; Nazar, L. F. (Curr. Opin. Solid State Mater. Sci., 2012)

(untitled) - Kim, S.-W.; Seo, D.-H.; Ma, X.; Ceder, G.; Kang, K. (Adv. Energy Mater., 2012)

(untitled) - Palomares, V.; Serras, P.; Villaluenga, I.; Hueso, K. B.; Carretero-González, J.; Rojo, T. (Energy Environ. Sci., 2012)

(untitled) - Pan, H. L.; Hu, Y. S.; Chen, L. Q. (Energy Environ. Sci., 2013)

(untitled) - Slater, M. D.; Kim, D.; Lee, E.; Johnson, C. S. (Adv. Funct. Mater., 2013)

(untitled) - Klein, F.; Jache, B.; Bhide, A.; Adelhelm, P. (Phys. Chem. Chem. Phys., 2013)

Lehrbuch der Anorganischen Chemie - Holleman, A.; Wiberg, N. (De Gruyter, 2007)

(untitled) - Wen, Z.; Cao, J.; Gu, Z.; Xu, X.; Zhang, F.; Lin, Z. (Solid State Ionics, 2008)

Linden’s Handbook of Batteries - Akhil, A. A.; Boyes, J. D.; Bulter, P. C.; Doughty, D. H. (Batteries for electrical energy storage applications, 2011)

(untitled) - Hueso, K. B.; Armand, M.; Rojo, T. (Energy Environ. Sci., 2013)

(untitled) - Oshima, T.; Kajita, M.; Okuno, A. (Int. J. Appl. Ceram. Technol., 2004)

(untitled) - Hartmann, P.; Leichtweiss, T.; Busche, M. R.; Schneider, M.; Reich, M.; Sann, J.; Adelhelm, P.; Janek, J. (J. Phys. Chem. C, 2013)

(untitled) - Eufinger, J.-P.; Schmidt, A.; Lerch, M.; Janek, J. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Sangster, J.; Pelton, A. D. (J. Phase Equilib., 1992)

(untitled) - Wriedt, H. A. (Bull. Alloy Phase Diagrams, 1987)

(untitled) - Ren, X.; Wu, Y. (J. Am. Chem. Soc., 2013)

(untitled) - Ren, X.; Lau, K. C.; Yu, M.; Bi, X.; Kreidler, E.; Curtiss, L. A.; Wu, Y. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Girishkumar, G.; McCloskey, B.; Luntz, A. C.; Swanson, S.; Wilcke, W. (J. Phys. Chem. Lett., 2010)

(untitled) - Christensen, J.; Albertus, P.; Sanchez-Carrera, R. S.; Lohmann, T.; Kozinsky, B.; Liedtke, R.; Ahmed, J.; Kojic, A. (J. Electrochem. Soc., 2012)

(untitled) - Visco, S. J.; Nimon, V. Y.; Petrov, A.; Pridatko, K.; Goncharenko, N.; Nimon, E.; De Jonghe, L.; Volfkovich, Y. M.; Bograchev, D. A. (J. Solid State Electrochem., 2014)

(untitled) - Gallagher, K. G.; Goebel, S.; Greszler, T.; Mathias, M.; Oelerich, W.; Eroglu, D.; Srinivasan, V. (Energy Environ. Sci., 2014)

(untitled) - Peled, E.; Golodnitsky, D.; Mazor, H.; Goor, M.; Avshalomov, S. (J. Power Sources, 2011)

(untitled) - Bender, C. L.; Hartmann, P.; Vračar, M.; Adelhelm, P.; Janek, J. (Adv. Energy Mater., 2014)

(untitled) - Lyall, A. E. (1971)

(untitled) - Abraham, K. M.; Jiang, Z. (J. Electrochem. Soc., 1996)

(untitled) - Read, J. (J. Electrochem. Soc., 2002)

(untitled) - Débart, A.; Paterson, A. J.; Bao, J.; Bruce, P. G. (Angew. Chem., Int. Ed. Engl., 2008)

(untitled) - Lu, Y.-C.; Gallant, B. M.; Kwabi, D. G.; Harding, J. R.; Mitchell, R. R.; Whittingham, M. S.; Shao-Horn, Y. (Energy Environ. Sci., 2013)

(untitled) - Zhou, G.; Pei, S.; Li, L.; Wang, D.-W.; Wang, S.; Huang, K.; Yin, L.-C.; Li, F.; Cheng, H.-M. (Adv. Mater., 2014)

(untitled) - Garcia-Araez, N.; Novák, P. (J. Solid State Electrochem., 2013)

(untitled) - Débart, A.; Bao, J.; Armstrong, G.; Bruce, P. G. (J. Power Sources, 2007)

(untitled) - Jin, L.; Xu, L.; Morein, C.; Chen, C.-H.; Lai, M.; Dharmarathna, S.; Dobley, A.; Suib, S. L. (Adv. Funct. Mater., 2010)

(untitled) - Ominde, N.; Bartlett, N.; Yang, X.-Q.; Qu, D. (J. Power Sources, 2008)

(untitled) - Zhang, G. Q.; Zheng, J. P.; Liang, R.; Zhang, C.; Wang, B.; Au, M.; Hendrickson, M.; Plichta, E. J. (J. Electrochem. Soc., 2011)

(untitled) - Lu, Y.-C.; Xu, Z.; Gasteiger, H. A.; Chen, S.; Hamad-Schifferli, K.; Shao-Horn, Y. (J. Am. Chem. Soc., 2010)

(untitled) - Cheng, H.; Scott, K. (Appl. Catal., B: Environ., 2011)

(untitled) - Lu, J.; Lei, Y.; Lau, K. C.; Luo, X.; Du, P.; Wen, J.; Assary, R. S.; Das, U.; Miller, D. J.; Elam, J. W.; Albishri, H. M.; El-Hady, D. A.; et al. (Nat. Commun., 2013)

(untitled) - McCloskey, B. D.; Scheffler, R.; Speidel, A.; Bethune, D. S.; Shelby, R. M.; Luntz, A. C. (J. Am. Chem. Soc., 2011)

(untitled) - Xu, K. (Chem. Rev., 2004)

(untitled) - Mizuno, F.; Nakanishi, S.; Kotani, Y.; Yokoishi, S.; Iba, H. (Electrochemistry, 2010)

(untitled) - Freunberger, S. A.; Chen, Y.; Peng, Z.; Griffin, J. M.; Hardwick, L. J.; Bardé, F.; Novák, P.; Bruce, P. G. (J. Am. Chem. Soc., 2011)

(untitled) - McCloskey, B. D.; Bethune, D. S.; Shelby, R. M.; Girishkumar, G.; Luntz, A. C. (J. Phys. Chem. Lett., 2011)

(untitled) - Veith, G. M.; Dudney, N. J.; Howe, J.; Nanda, J. (J. Phys. Chem. C, 2011)

(untitled) - Xu, W.; Viswanathan, V. V.; Wang, D.; Towne, S. A.; Xiao, J.; Nie, Z.; Hu, D.; Zhang, J.-G. (J. Power Sources, 2011)

(untitled) - Bryantsev, V. S.; Giordani, V.; Walker, W.; Blanco, M.; Zecevic, S.; Sasaki, K.; Uddin, J.; Addison, D.; Chase, G. V. (J. Phys. Chem. A, 2011)

(untitled) - Laino, T.; Curioni, A. (Chemistry, 2012)

(untitled) - Hyoung Oh, S.; Yim, T.; Pomerantseva, E.; Nazar, L. F. (Electrochem. Solid-State Lett., 2011)

(untitled) - Chalasani, D.; Lucht, B. L. (ECS Electrochem. Lett., 2012)

(untitled) - Veith, G. M.; Nanda, J.; Delmau, L. H.; Dudney, N. J. (J. Phys. Chem. Lett., 2012)

(untitled) - Aurbach, D.; Daroux, M.; Faguy, P.; Yeager, E. (J. Electroanal. Chem., 1991)

(untitled) - Mizuno, F.; Takechi, K.; Higashi, S.; Shiga, T.; Shiotsuki, T.; Takazawa, N.; Sakurabayashi, Y.; Okazaki, S.; Nitta, I.; Kodama, T.; Nakamoto, H.; Nishikoori, H.; et al. (J. Power Sources, 2013)

(untitled) - Cecchetto, L.; Salomon, M.; Scrosati, B.; Croce, F. (J. Power Sources, 2012)

(untitled) - Allen, C. J.; Mukerjee, S.; Plichta, E. J.; Hendrickson, M. A.; Abraham, K. M. (J. Phys. Chem. Lett., 2011)

(untitled) - Xu, D.; Wang, Z.-L.; Xu, J.-J.; Zhang, L.-L.; Zhang, X.-B. (Chem. Commun., 2012)

(untitled) - Trahan, M. J.; Mukerjee, S.; Plichta, E. J.; Hendrickson, M. A.; Abraham, K. M. (J. Electrochem. Soc., 2012)

(untitled) - Chen, Y.; Freunberger, S. A.; Peng, Z.; Bardé, F.; Bruce, P. G. (J. Am. Chem. Soc., 2012)

(untitled) - Giordani, V.; Walker, W.; Bryantsev, V. S.; Uddin, J.; Chase, G. V.; Addison, D. (J. Electrochem. Soc., 2013)

(untitled) - Wang, H.; Liao, X.-Z.; Li, L.; Chen, H.; Jiang, Q.-Z.; He, Y.-S.; Ma, Z.-F. (J. Electrochem. Soc., 2012)

(untitled) - Zhang, Z.; Lu, J.; Assary, R. S.; Du, P.; Wang, H.-H.; Sun, Y.-K.; Qin, Y.; Lau, K. C.; Greeley, J.; Redfern, P. C.; Iddir, H.; Curtiss, L. A.; et al. (J. Phys. Chem. C, 2011)

(untitled) - Xu, D.; Wang, Z.-L.; Xu, J.-J.; Zhang, L.-L.; Wang, L.-M.; Zhang, X.-B. (Chem. Commun., 2012)

(untitled) - Sharon, D.; Etacheri, V.; Garsuch, A.; Afri, M.; Frimer, A. A.; Aurbach, D. (J. Phys. Chem. Lett., 2013)

(untitled) - Meini, S.; Tsiouvaras, N.; Schwenke, K. U.; Piana, M.; Beyer, H.; Lange, L.; Gasteiger, H. A. (Phys. Chem. Chem. Phys., 2013)

(untitled) - McCloskey, B. D.; Garcia, J. M.; Luntz, A. C. (J. Phys. Chem. Lett., 2014)

(untitled) - McCloskey, B. D.; Bethune, D. S.; Shelby, R. M.; Mori, T.; Scheffler, R.; Speidel, A.; Sherwood, M.; Luntz, A. C. (J. Phys. Chem. Lett., 2012)

(untitled) - Freunberger, S. A.; Chen, Y.; Drewett, N. E.; Hardwick, L. J.; Bardé, F.; Bruce, P. G. (Angew. Chem., Int. Ed. Engl., 2011)

(untitled) - Adams, B. D.; Black, R.; Williams, Z.; Fernandes, R.; Cuisinier, M.; Berg, E. J.; Novak, P.; Murphy, G. K.; Nazar, L. F. (Adv. Energy Mater., 2015)

(untitled) - Kang, S. J.; Mori, T.; Narizuka, S.; Wilcke, W.; Kim, H. C. (Nat. Commun., 2014)

(untitled) - Xu, W.; Xu, K.; Viswanathan, V. V.; Towne, S. A.; Hardy, J. S.; Xiao, J.; Nie, Z.; Hu, D.; Wang, D.; Zhang, J.-G. (J. Power Sources, 2011)

(untitled) - Walker, W.; Giordani, V.; Uddin, J.; Bryantsev, V. S.; Chase, G. V.; Addison, D. (J. Am. Chem. Soc., 2013)

(untitled) - Tsiouvaras, N.; Meini, S.; Buchberger, I.; Gasteiger, H. A. (J. Electrochem. Soc., 2013)

(untitled) - Novák, P.; Panitz, J.-C.; Joho, F.; Lanz, M.; Imhof, R.; Coluccia, M. (J. Power Sources, 2000)

(untitled) - Barile, C. J.; Gewirth, A. A. (J. Electrochem. Soc., 2013)

(untitled) - Armstrong, A. R.; Holzapfel, M.; Novák, P.; Johnson, C. S.; Kang, S.-H.; Thackeray, M. M.; Bruce, P. G. (J. Am. Chem. Soc., 2006)

(untitled) - Hartmann, P.; Bender, C. L.; Sann, J.; Dürr, A. K.; Jansen, M.; Janek, J.; Adelhelm, P. (Phys. Chem. Chem. Phys., 2013)

(untitled) - McCloskey, B. D.; Valery, A.; Luntz, A. C.; Gowda, S. R.; Wallraff, G. M.; Garcia, J. M.; Mori, T.; Krupp, L. E. (J. Phys. Chem. Lett., 2013)

(untitled) - Hase, Y.; Ito, E.; Shiga, T.; Mizuno, F.; Nishikoori, H.; Iba, H.; Takechi, K. (Chem. Commun., 2013)

(untitled) - Black, R.; Oh, S. H.; Lee, J.-H.; Yim, T.; Adams, B.; Nazar, L. F. (J. Am. Chem. Soc., 2012)

(untitled) - McCloskey, B. D.; Speidel, A.; Scheffler, R.; Miller, D. C.; Viswanathan, V.; Hummelshøj, J. S.; Nørskov, J. K.; Luntz, A. C. (J. Phys. Chem. Lett., 2012)

(untitled) - Ottakam Thotiyl, M. M.; Freunberger, S. A.; Peng, Z.; Bruce, P. G. (J. Am. Chem. Soc., 2013)

(untitled) - Ottakam Thotiyl, M. M.; Freunberger, S. A.; Peng, Z.; Chen, Y.; Liu, Z.; Bruce, P. G. (Nat. Mater., 2013)

(untitled) - Younesi, R.; Norby, P.; Vegge, T. (ECS Electrochem. Lett., 2014)

(untitled) - Sharon, D.; Afri, M.; Noked, M.; Garsuch, A.; Frimer, A. A.; Aurbach, D. (J. Phys. Chem. Lett., 2013)

(untitled) - Adams, B. D.; Radtke, C.; Black, R.; Trudeau, M. L.; Zaghib, K.; Nazar, L. F. (Energy Environ. Sci., 2013)

(untitled) - Radin, M. D.; Siegel, D. J. (Energy Environ. Sci., 2013)

(untitled) - Radin, M. D.; Rodriguez, J. F.; Tian, F.; Siegel, D. J. (J. Am. Chem. Soc., 2012)

(untitled) - Garcia-Lastra, J. M.; Myrdal, J. S. G.; Christensen, R.; Thygesen, K. S.; Vegge, T. (J. Phys. Chem. C, 2013)

(untitled) - Gerbig, O.; Merkle, R.; Maier, J. (Adv. Mater., 2013)

(untitled) - Viswanathan, V.; Thygesen, K. S.; Hummelshøj, J. S.; Nørskov, J. K.; Girishkumar, G.; McCloskey, B. D.; Luntz, A. C. (J. Chem. Phys., 2011)

(untitled) - Luntz, A. C.; Viswanathan, V.; Voss, J.; Varley, J. B.; Nørskov, J. K.; Scheffler, R.; Speidel, A. (J. Phys. Chem. Lett., 2013)

(untitled) - Aetukuri, N. B.; McCloskey, B. D.; Garcia, J. M.; Krupp, L. E.; Viswanathan, V.; Luntz, A. C. (arXiv [cond-mat.mtrl-sci], 2014)

(untitled) - Zheng, H.; Xiao, D.; Li, X.; Liu, Y.; Wu, Y.; Wang, J.; Jiang, K.; Chen, C.; Gu, L.; Wei, X.; Hu, Y.-S.; Chen, Q.; et al. (Nano Lett., 2014)

(untitled) - Chase, G. V.; Zecevic, S.; Walker, W.; Uddin, J.; Sasaki, K. A.; Giordani, V.; Bryantsev, V. S.; Blanco, M.; Addison, D. (2011)

(untitled) - Chen, Y.; Freunberger, S. A.; Peng, Z.; Fontaine, O.; Bruce, P. G. (Nat. Chem., 2013)

(untitled) - Lim, H.-D.; Song, H.; Kim, J.; Gwon, H.; Bae, Y.; Park, K.-Y.; Hong, J.; Kim, H.; Kim, T.; Kim, Y. H.; Lepró, X.; Ovalle-Robles, R.; et al. (Angew. Chem., 2014)

(untitled) - Bergner, B. J.; Schürmann, A.; Peppler, K.; Garsuch, A.; Janek, J. (J. Am. Chem. Soc., 2014)

(untitled) - Lopez, N.; Graham, D. J.; McGuire, R., Jr; Alliger, G. E.; Shao-Horn, Y.; Cummins, C. C.; Nocera, D. G. (Science, 2012)

(untitled) - Sun, Q.; Yang, Y.; Fu, Z.-W. (Electrochem. Commun., 2012)

(untitled) - Das, S. K.; Xu, S.; Archer, L. A. (Electrochem. Commun., 2013)

(untitled) - Liu, W.; Sun, Q.; Yang, Y.; Xie, J.-Y.; Fu, Z.-W. (Chem. Commun., 2013)

(untitled) - Li, Y.; Yadegari, H.; Li, X.; Banis, M. N.; Li, R.; Sun, X. (Chem. Commun., 2013)

(untitled) - Liu, W.-M.; Yin, W.-W.; Ding, F.; Sang, L.; Fu, Z.-W. (Electrochem. Commun., 2014)

(untitled) - Kim, J.; Lim, H.-D.; Gwon, H.; Kang, K. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Jian, Z.; Chen, Y.; Li, F.; Zhang, T.; Liu, C.; Zhou, H. (J. Power Sources, 2014)

(untitled) - Yadegari, H.; Li, Y.; Norouzi Banis, M.; Li, X.; Wang, B.; Sun, Q.; Li, R.; Sham, T.-K.; Cui, X.; Sun, X. (Energy Environ. Sci., 2014)

(untitled) - Hartmann, P.; Bender, C. L.; Vračar, M.; Dürr, A. K.; Garsuch, A.; Janek, J.; Adelhelm, P. (Nat. Mater., 2013)

(untitled) - Hartmann, P.; Grübl, D.; Sommer, H.; Janek, J.; Bessler, W. G.; Adelhelm, P. (J. Phys. Chem. C, 2014)

(untitled) - Zhao, N.; Li, C.; Guo, X. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Das, S. K.; Lau, S.; Archer, L. A. (J. Mater. Chem. A, 2014)

(untitled) - Ha, S.; Kim, J.-K.; Choi, A.; Kim, Y.; Lee, K. T. (ChemPhysChem, 2014)

(untitled) - Peled, E.; Golodnitsky, D.; Hadar, R.; Mazor, H.; Goor, M.; Burstein, L. (J. Power Sources, 2013)

(untitled) - Lee, B.; Seo, D.-H.; Lim, H.-D.; Park, I.; Park, K.-Y.; Kim, J.; Kang, K. (Chem. Mater., 2014)

(untitled) - Kang, S.; Mo, Y.; Ong, S. P.; Ceder, G. (Nano Lett., 2014)

(untitled) - Stephanou, S. E.; Schechter, W. H.; Argersinger, W. J.; Kleinberg, J. (J. Am. Chem. Soc., 1949)

(untitled) - Xu, S.; Lu, Y.; Wang, H.; Abruña, H. D.; Archer, L. A. (J. Mater. Chem. A, 2014)

(untitled) - Hayashi, K.; Shima, K.; Sugiyama, F. (J. Electrochem. Soc., 2013)

(untitled) - Rao, M. L. B. (1968)

(untitled) - Rauh, R. D.; Abraham, K. M.; Pearson, G. F.; Surprenant, J. K.; Brummer, S. B. (J. Electrochem. Soc., 1979)

(untitled) - Abraham, K. M. (J. Power Sources, 1981)

(untitled) - Mikhaylik, Y. V.; Akridge, J. R. (J. Electrochem. Soc., 2004)

(untitled) - Busche, M. R.; Adelhelm, P.; Sommer, H.; Schneider, H.; Leitner, K.; Janek, J. (J. Power Sources, 2014)

(untitled) - Raiß, C.; Peppler, K.; Janek, J.; Adelhelm, P. (Carbon, 2014)

(untitled) - Kumaresan, K.; Mikhaylik, Y.; White, R. E. (J. Electrochem. Soc., 2008)

(untitled) - Waluś, S.; Barchasz, C.; Colin, J.-F.; Martin, J.-F.; Elkaïm, E.; Leprêtre, J.-C.; Alloin, F. (Chem. Commun., 2013)

(untitled) - Schneider, H.; Gollub, C.; Weiss, T.; Kulisch, J.; Leitner, K.; Schmidt, R.; Safont-Sempere, M. M.; Mikhaylik, Y.; Kelley, T.; Scordilis-Kelley, C.; Laramie, M.; Du, H. (J. Electrochem. Soc., 2014)

(untitled) - Okamoto, H. (J. Phase Equilib., 1995)

(untitled) - Sangster, J.; Pelton, A. D. (J. Phase Equilib., 1997)

(untitled) - Kulisch, J.; Sommer, H.; Brezesinski, T.; Janek, J. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Urbonaite, S.; Novák, P. (J. Power Sources, 2014)

(untitled) - Huang, J. P.; Yuan, D. D.; Zhang, H. Z.; Cao, Y. L.; Li, G. R.; Yang, H. X.; Gao, X. P. (RSC Adv., 2013)

(untitled) - Brückner, J.; Thieme, S.; Grossmann, H. T.; Dörfler, S.; Althues, H.; Kaskel, S. (J. Power Sources, 2014)

(untitled) - Hagen, M.; Fanz, P.; Tübke, J. (J. Power Sources, 2014)

(untitled) - Kang, S.-H.; Zhao, X.; Manuel, J.; Ahn, H.-J.; Kim, K.-W.; Cho, K.-K.; Ahn, J.-H. (Phys. Status Solidi A, 2014)

(untitled) - Song, J.; Xu, T.; Gordin, M. L.; Zhu, P.; Lv, D.; Jiang, Y.-B.; Chen, Y.; Duan, Y.; Wang, D. (Adv. Funct. Mater., 2014)

(untitled) - Yang, Y.; Zheng, G.; Cui, Y. (Energy Environ. Sci., 2013)

(untitled) - Lin, Z.; Liu, Z.; Fu, W.; Dudney, N. J.; Liang, C. (Angew. Chem., Int. Ed., 2013)

(untitled) - Hassoun, J.; Scrosati, B. (Adv. Mater., 2010)

(untitled) - Nagata, H.; Chikusa, H. (J. Power Sources, 2014)

S. P. Corporation

O. E. Ltd.

Linden’s Handbook of Batteries - Doughty, D. H. (Rechargeable Lithium Metal Batteries (Ambient Temperature), 2011)

(untitled) - Gordon, J.; Watkins, J. (2010)

(untitled) - Lu, X.; Kirby, B. W.; Xu, W.; Li, G.; Kim, J. Y.; Lemmon, J. P.; Sprenkle, V. L.; Yang, Z. (Energy Environ. Sci., 2013)

(untitled) - Lu, X.; Li, G.; Kim, J. Y.; Mei, D.; Lemmon, J. P.; Sprenkle, V. L.; Liu, J. (Nat. Commun., 2014)

(untitled) - Weddigen, G. (J. Electrochem. Soc., 1980)

(untitled) - Ji, X.; Nazar, L. F. (J. Mater. Chem., 2010)

(untitled) - Etacheri, V.; Marom, R.; Elazari, R.; Salitra, G.; Aurbach, D. (Energy Environ. Sci., 2011)

(untitled) - Barghamadi, M.; Kapoor, A.; Wen, C. (J. Electrochem. Soc., 2013)

(untitled) - Manthiram, A.; Fu, Y.; Chung, S.-H.; Zu, C.; Su, Y.-S. (Chem. Rev., 2014)

(untitled) - Yin, Y.-X.; Xin, S.; Guo, Y.-G.; Wan, L.-J. (Angew. Chem., Int. Ed. Engl., 2013)

(untitled) - Chen, L.; Shaw, L. L. (J. Power Sources, 2014)

(untitled) - Zhang, S. S. (J. Power Sources, 2013)

(untitled) - Wang, J.; Liu, L.; Ling, Z.; Yang, J.; Wan, C.; Jiang, C. (Electrochim. Acta, 2003)

(untitled) - Jayaprakash, N.; Shen, J.; Moganty, S. S.; Corona, A.; Archer, L. A. (Angew. Chem., 2011)

(untitled) - Cheon, S.-E.; Cho, J.-H.; Ko, K.-S.; Kwon, C.-W.; Chang, D.-R.; Kim, H.-T.; Kim, S.-W. (J. Electrochem. Soc., 2002)

(untitled) - Lacey, M. J.; Jeschull, F.; Edström, K.; Brandell, D. (Chem. Commun., 2013)

(untitled) - Sun, J.; Huang, Y.; Wang, W.; Yu, Z.; Wang, A.; Yuan, K. (Electrochim. Acta, 2008)

(untitled) - Wang, Q.; Wang, W.; Huang, Y.; Wang, F.; Zhang, H.; Yu, Z.; Wang, A.; Yuan, K. (J. Electrochem. Soc., 2011)

(untitled) - Jung, Y.; Kim, S. (Electrochem. Commun., 2007)

(untitled) - He, M.; Yuan, L.-X.; Zhang, W.-X.; Hu, X.-L.; Huang, Y.-H. (J. Phys. Chem. C, 2011)

(untitled) - Wang, J. L.; Yang, J.; Xie, J. Y.; Xu, N. X.; Li, Y. (Electrochem. Commun., 2002)

(untitled) - Zhang, B.; Qin, X.; Li, G. R.; Gao, X. P. (Energy Environ. Sci., 2010)

(untitled) - Meyer, B. (Chem. Rev., 1976)

(untitled) - Ye, H.; Yin, Y.-X.; Xin, S.; Guo, Y.-G. (J. Mater. Chem. A, 2013)

Chemistry of the Elements - Greenwood, N. N.; Earnshaw, A. (Elsevier Science, 1997)

(untitled) - Xin, S.; Gu, L.; Zhao, N.-H.; Yin, Y.-X.; Zhou, L.-J.; Guo, Y.-G.; Wan, L.-J. (J. Am. Chem. Soc., 2012)

(untitled) - Elazari, R.; Salitra, G.; Garsuch, A.; Panchenko, A.; Aurbach, D. (Adv. Mater., 2011)

(untitled) - Li, X.; Cao, Y.; Qi, W.; Saraf, L. V.; Xiao, J.; Nie, Z.; Mietek, J.; Zhang, J.-G.; Schwenzer, B.; Liu, J. (J. Mater. Chem., 2011)

(untitled) - Ryu, H. S.; Park, J. W.; Park, J.; Ahn, J.-P.; Kim, K.-W.; Ahn, J.-H.; Nam, T.-H.; Wang, G.; Ahn, H.-J. (J. Mater. Chem. A, 2013)

(untitled) - Guo, J.; Xu, Y.; Wang, C. (Nano Lett., 2011)

(untitled) - Zheng, G.; Yang, Y.; Cha, J. J.; Hong, S. S.; Cui, Y. (Nano Lett., 2011)

(untitled) - Tachikawa, N.; Yamauchi, K.; Takashima, E.; Park, J.-W.; Dokko, K.; Watanabe, M. (Chem. Commun., 2011)

(untitled) - Wang, J.; Yang, J.; Xie, J.; Xu, N. (Adv. Mater., 2002)

(untitled) - Liang, C.; Dudney, N. J.; Howe, J. Y. (Chem. Mater., 2009)

(untitled) - Ji, X.; Lee, K. T.; Nazar, L. F. (Nat. Mater., 2009)

(untitled) - He, G.; Ji, X.; Nazar, L. (Energy Environ. Sci., 2011)

(untitled) - Wei Seh, Z.; Li, W.; Cha, J. J.; Zheng, G.; Yang, Y.; McDowell, M. T.; Hsu, P.-C.; Cui, Y. (Nat. Commun., 2013)

(untitled) - Rao, M.; Song, X.; Cairns, E. J. (J. Power Sources, 2012)

(untitled) - Cao, Y.; Li, X.; Aksay, I. A.; Lemmon, J.; Nie, Z.; Yang, Z.; Liu, J. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Wang, X.; Wang, Z.; Chen, L. (J. Power Sources, 2013)

(untitled) - Wang, H.; Yang, Y.; Liang, Y.; Robinson, J. T.; Li, Y.; Jackson, A.; Cui, Y.; Dai, H. (Nano Lett., 2011)

(untitled) - Dörfler, S.; Hagen, M.; Althues, H.; Tübke, J.; Kaskel, S.; Hoffmann, M. J. (Chem. Commun., 2012)

(untitled) - Hagen, M.; Dörfler, S.; Althues, H.; Tübke, J.; Hoffmann, M. J.; Kaskel, S.; Pinkwart, K. (J. Power Sources, 2012)

(untitled) - Zhou, G.; Wang, D.-W.; Li, F.; Hou, P.-X.; Yin, L.; Liu, C.; Lu, G. Q. M.; Gentle, I. R.; Cheng, H.-M. (Energy Environ. Sci., 2012)

(untitled) - Su, Y.-S.; Fu, Y.; Manthiram, A. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Yang, Y.; McDowell, M. T.; Jackson, A.; Cha, J. J.; Hong, S. S.; Cui, Y. (Nano Lett., 2010)

(untitled) - Hassoun, J.; Sun, Y.-K.; Scrosati, B. (J. Power Sources, 2011)

(untitled) - Hassoun, J.; Scrosati, B. (Angew. Chem., Int. Ed., 2010)

(untitled) - Hassoun, J.; Kim, J.; Lee, D.-J.; Jung, H.-G.; Lee, S.-M.; Sun, Y.-K.; Scrosati, B. (J. Power Sources, 2012)

(untitled) - Whittingham, S. (1977)

(untitled) - Yang, Y.; Zheng, G.; Misra, S.; Nelson, J.; Toney, M.; Cui, Y. (J. Am. Chem. Soc., 2012)

(untitled) - Cai, K.; Song, M.-K.; Cairns, E. J.; Zhang, Y. (Nano Lett., 2012)

(untitled) - Zheng, S.; Chen, Y.; Xu, Y.; Yi, F.; Zhu, Y.; Liu, Y.; Yang, J.; Wang, C. (ACS Nano, 2013)

(untitled) - Yang, Z.; Guo, J.; Das, S. K.; Yu, Y.; Zhou, Z.; Abruña, H. D.; Archer, L. A. (J. Mater. Chem. A, 2013)

(untitled) - Guo, J.; Yang, Z.; Yu, Y.; Abruña, H. D.; Archer, L. A. (J. Am. Chem. Soc., 2012)

(untitled) - Lin, Z.; Liu, Z.; Dudney, N. J.; Liang, C. (ACS Nano, 2013)

(untitled) - Chang, D.-R.; Lee, S.-H.; Kim, S.-W.; Kim, H.-T. (J. Power Sources, 2002)

(untitled) - Wang, W.; Wang, Y.; Huang, Y.; Huang, C.; Yu, Z.; Zhang, H.; Wang, A.; Yuan, K. (J. Appl. Electrochem., 2010)

(untitled) - Kim, S.; Jung, Y.; Lim, H. (Electrochim. Acta, 2004)

(untitled) - Peled, E.; Sternberg, Y.; Gorenshtein, A.; Lavi, Y. (J. Electrochem. Soc., 1989)

(untitled) - Shim, J.; Striebel, K. A.; Cairns, E. J. (J. Electrochem. Soc., 2002)

(untitled) - Gao, J.; Lowe, M. A.; Kiya, Y.; Abruña, H. D. (J. Phys. Chem. C, 2011)

(untitled) - Aurbach, D. (J. Power Sources, 2000)

(untitled) - Kim, S.; Jung, Y.; Park, S.-J. (Electrochim. Acta, 2007)

(untitled) - Barchasz, C.; Leprêtre, J.-C.; Patoux, S.; Alloin, F. (Electrochim. Acta, 2013)

(untitled) - Mikhaylik, Y. V.; Kovalev, I.; Schock, R.; Kumaresan, K.; Xu, J.; Affinito, J. (ECS Trans., 2010)

(untitled) - Aurbach, D.; Pollak, E.; Elazari, R.; Salitra, G.; Kelley, C. S.; Affinito, J. (J. Electrochem. Soc., 2009)

(untitled) - Xiong, S.; Xie, K.; Diao, Y.; Hong, X. (J. Power Sources, 2014)

(untitled) - Mikhaylik, Y. V. (2008)

(untitled) - Liang, X.; Wen, Z.; Liu, Y.; Zhang, H.; Huang, L.; Jin, J. (J. Power Sources, 2011)

(untitled) - Gorkovenko, A. (2008)

(untitled) - Zhang, S. S. (Electrochim. Acta, 2012)

(untitled) - Suo, L.; Hu, Y.-S.; Li, H.; Armand, M.; Chen, L. (Nat. Commun., 2013)

(untitled) - Cuisinier, M.; Cabelguen, P.-E.; Adams, B. D.; Garsuch, A.; Balasubramanian, M.; Nazar, L. F. (Energy Environ. Sci., 2014)

(untitled) - Park, J.-W.; Yamauchi, K.; Takashima, E.; Tachikawa, N.; Ueno, K.; Dokko, K.; Watanabe, M. (J. Phys. Chem. C, 2013)

(untitled) - Wang, L.; Byon, H. R. (J. Power Sources, 2013)

(untitled) - Marmorstein, D.; Yu, T. H.; Striebel, K. A.; McLarnon, F. R.; Hou, J.; Cairns, E. J. (J. Power Sources, 2000)

(untitled) - Visco, S.; Nimon, Y. (Aqueous electrolyte lithium sulfur batteries, 2014)

(untitled) - Visco, S. J.; Nimon, V. Y.; Petrov, A.; Pridatko, K.; Goncharenko, N.; Nimon, E.; De Jonghe, L.; Volfkovich, Y. M.; Bograchev, D. A. (J. Solid State Electrochem., 2014)

(untitled) - Kim, H.; Jeong, G.; Kim, Y.-U.; Kim, J.-H.; Park, C.-M.; Sohn, H.-J. (Chem. Soc. Rev., 2013)

(untitled) - Lee, Y. M.; Choi, N.-S.; Park, J. H.; Park, J.-K. (J. Power Sources, 2003)

(untitled) - Mikhaylik, Y. V. (Electrolytes for lithium sulfur cells, 2004)

(untitled) - Lin, Z.; Liu, Z.; Fu, W.; Dudney, N. J.; Liang, C. (Adv. Funct. Mater., 2013)

(untitled) - Ding, F.; Xu, W.; Graff, G. L.; Zhang, J.; Sushko, M. L.; Chen, X.; Shao, Y.; Engelhard, M. H.; Nie, Z.; Xiao, J.; Liu, X.; Sushko, P. V.; et al. (J. Am. Chem. Soc., 2013)

(untitled) - Liu, N.; Hu, L.; McDowell, M. T.; Jackson, A.; Cui, Y. (ACS Nano, 2011)

(untitled) - Magasinski, A.; Dixon, P.; Hertzberg, B.; Kvit, A.; Ayala, J.; Yushin, G. (Nat. Mater., 2010)

(untitled) - Brückner, J.; Thieme, S.; Böttger-Hiller, F.; Bauer, I.; Grossmann, H. T.; Strubel, P.; Althues, H.; Spange, S.; Kaskel, S. (Adv. Funct. Mater., 2014)

(untitled) - Fronczek, D. N.; Bessler, W. G. (J. Power Sources, 2013)

(untitled) - Barchasz, C.; Molton, F.; Duboc, C.; Leprêtre, J.-C.; Patoux, S.; Alloin, F. (Anal. Chem., 2012)

(untitled) - Nelson, J.; Misra, S.; Yang, Y.; Jackson, A.; Liu, Y.; Wang, H.; Dai, H.; Andrews, J. C.; Cui, Y.; Toney, M. F. (J. Am. Chem. Soc., 2012)

(untitled) - Cañas, N. A.; Wolf, S.; Wagner, N.; Friedrich, K. A. (J. Power Sources, 2013)

(untitled) - Ryu, H. S.; Guo, Z.; Ahn, H. J.; Cho, G. B.; Liu, H. (J. Power Sources, 2009)

(untitled) - Yuan, L.; Qiu, X.; Chen, L.; Zhu, W. (J. Power Sources, 2009)

(untitled) - Akridge, J. R.; Mikhaylik, Y. V.; White, N. (Solid State Ionics, 2004)

(untitled) - Cheon, S.-E.; Ko, K.-S.; Cho, J.-H.; Kim, S.-W.; Chin, E.-Y.; Kim, H.-T. (J. Electrochem. Soc., 2003)

(untitled) - Ryu, H.-S.; Ahn, H.-J.; Kim, K.-W.; Ahn, J.-H.; Lee, J.-Y. (J. Power Sources, 2006)

(untitled) - Patel, M. U. M.; Demir-Cakan, R.; Morcrette, M.; Tarascon, J.-M.; Gaberscek, M.; Dominko, R. (ChemSusChem, 2013)

(untitled) - Cuisinier, M.; Cabelguen, P.-E.; Evers, S.; He, G.; Kolbeck, M.; Garsuch, A.; Bolin, T.; Balasubramanian, M.; Nazar, L. F. (J. Phys. Chem. Lett., 2013)

(untitled) - Visco, S. J.; Katz, B. D.; Nimon, Y. S.; De Jonghe, L. C. (2012)

(untitled) - Jin, Z.; Xie, K.; Hong, X.; Hu, Z.; Liu, X. (J. Power Sources, 2012)

(untitled) - Huang, J.-Q.; Zhang, Q.; Peng, H.-J.; Liu, X.-Y.; Qian, W.-Z.; Wei, F. (Energy Environ. Sci., 2014)

(untitled) - Li, W.; Hicks-Garner, J.; Wang, J.; Liu, J.; Gross, A. F.; Sherman, E.; Graetz, J.; Vajo, J. J.; Liu, P. (Chem. Mater., 2014)

(untitled) - Vizintin, A.; Patel, M. U. M.; Genorio, B.; Dominko, R. (ChemElectroChem, 2014)

(untitled) - Kobayashi, T.; Imade, Y.; Shishihara, D.; Homma, K.; Nagao, M.; Watanabe, R.; Yokoi, T.; Yamada, A.; Kanno, R.; Tatsumi, T. (J. Power Sources, 2008)

(untitled) - Hayashi, A.; Ohtomo, T.; Mizuno, F.; Tadanaga, K.; Tatsumisago, M. (Electrochem. Commun., 2003)

(untitled) - Kanno, R.; Hata, T.; Kawamoto, Y.; Irie, M. (Solid State Ionics, 2000)

(untitled) - Kanno, R.; Murayama, M. (J. Electrochem. Soc., 2001)

(untitled) - Seino, Y.; Ota, T.; Takada, K.; Hayashi, A.; Tatsumisago, M. (Energy Environ. Sci., 2014)

(untitled) - Kamaya, N.; Homma, K.; Yamakawa, Y.; Hirayama, M.; Kanno, R.; Yonemura, M.; Kamiyama, T.; Kato, Y.; Hama, S.; Kawamoto, K.; Mitsui, A. (Nat. Mater., 2011)

(untitled) - Yu, X.; Manthiram, A. (J. Phys. Chem. Lett., 2014)

(untitled) - Park, C.-W.; Ahn, J.-H.; Ryu, H.-S.; Kim, K.-W.; Ahn, H.-J. (Electrochem. Solid-State Lett., 2006)

(untitled) - Wang, J.; Yang, J.; Nuli, Y.; Holze, R. (Electrochem. Commun., 2007)

(untitled) - Kim, J.-S.; Ahn, H.-J.; Kim, I.-P.; Kim, K.-W.; Ahn, J.-H.; Park, C.-W.; Ryu, H.-S. (J. Solid State Electrochem., 2008)

(untitled) - Ryu, H.; Kim, T.; Kim, K.; Ahn, J.-H.; Nam, T.; Wang, G.; Ahn, H.-J. (J. Power Sources, 2011)

(untitled) - Lee, D.-J.; Park, J.-W.; Hasa, I.; Sun, Y.-K.; Scrosati, B.; Hassoun, J. (J. Mater. Chem. A, 2013)

(untitled) - Wenzel, S.; Metelmann, H.; Raiß, C.; Dürr, A. K.; Janek, J.; Adelhelm, P. (J. Power Sources, 2013)

(untitled) - Hwang, T. H.; Jung, D. S.; Kim, J.-S.; Kim, B. G.; Choi, J. W. (Nano Lett., 2013)

(untitled) - Xin, S.; Yin, Y.-X.; Guo, Y.-G.; Wan, L.-J. (Adv. Mater., 2014)

(untitled) - Bauer, I.; Kohl, M.; Althues, H.; Kaskel, S. (Chem. Commun., 2014)

(untitled) - Zheng, S.; Han, P.; Han, Z.; Li, P.; Zhang, H.; Yang, J. (Adv. Energy Mater., 2014)

(untitled) - Park, C.-W.; Ryu, H.-S.; Kim, K.-W.; Ahn, J.-H.; Lee, J.-Y.; Ahn, H.-J. (J. Power Sources, 2007)

(untitled) - Su, Y.-S.; Manthiram, A. (Nat. Commun., 2012)

(untitled) - Zu, C.; Su, Y. S.; Fu, Y.; Manthiram, A. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Yim, T.; Park, M.-S.; Yu, J.-S.; Kim, K. J.; Im, K. Y.; Kim, J.-H.; Jeong, G.; Jo, Y. N.; Woo, S.-G.; Kang, K. S.; Lee, I.; Kim, Y.-J. (Electrochim. Acta, 2013)